2006
DOI: 10.1029/2005jd005884
|View full text |Cite
|
Sign up to set email alerts
|

Numerical sensitivity studies on the impact of aerosol properties and drop freezing modes on the glaciation, microphysics, and dynamics of clouds

Abstract: [1] Numerical simulations were performed to investigate the effects of drop freezing in immersion and contact modes for a convective situation. For the description of heterogeneous drop freezing, new approaches were used considering the significantly different ice nucleating efficiencies of various ice nuclei. An air parcel model with a sectional two-dimensional description of the cloud microphysics was employed. Sensitivity studies were undertaken by varying the insoluble particle types as well as the soluble… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
135
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(136 citation statements)
references
References 37 publications
(51 reference statements)
1
135
0
Order By: Relevance
“…That investigation is expanded in the current work via analysis of the impact of aerosol properties on cloud liquid droplets, consequent immersion freezing and microphysical properties, and the resulting influences on cloud properties and lifetime. As in the work of Diehl et al (2006), influences of aerosol soluble mass fraction and insoluble mass type are investigated. However, unlike in that work, experiments are carried out utilizing twodimensional, cloud-resolving simulations of a mixed-phase stratiform layer in order to analyze the ultimate influence of aerosol properties on both cloud micro-and macrophysics.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…That investigation is expanded in the current work via analysis of the impact of aerosol properties on cloud liquid droplets, consequent immersion freezing and microphysical properties, and the resulting influences on cloud properties and lifetime. As in the work of Diehl et al (2006), influences of aerosol soluble mass fraction and insoluble mass type are investigated. However, unlike in that work, experiments are carried out utilizing twodimensional, cloud-resolving simulations of a mixed-phase stratiform layer in order to analyze the ultimate influence of aerosol properties on both cloud micro-and macrophysics.…”
Section: Introductionmentioning
confidence: 99%
“…Diehl et al (2006) investigated the effects of drop freezing in both the immersion and contact modes for a convective mixed-phase situation utilizing a parcel model. In this work, strong sensitivity to aerosol soluble mass and insoluble particle type were cited.…”
Section: Introductionmentioning
confidence: 99%
“…Recent modelling studies have begun to explore the effect of biological ice nucleation on cloud microphysics, dynamics and precipitation (Diehl et al, 2006;Hoose et al, 2010;Phillips et al, 2009). However, due to the limited understanding of the ice nucleation properties of biological particles, such modelling studies often have significant uncertainties.…”
Section: Introductionmentioning
confidence: 99%
“…No significant difference was observed in the ice nucleation ability of uncoated and sulfuric-acid-coated Arizona test dust particles (Knopf and Koop 2006). From the table in Diehl et al (2006), it can be seen that the warmest median freezing temperature in the contact mode was found for bacteria, followed by montmorillonite, leaf litter, pollen, kaolinite, and finally by soot particles. In the immersion mode, all biological particles showed higher median freezing temperatures than the mineral dust particles and soot.…”
Section: Introductionmentioning
confidence: 76%
“…Evidence of Asian desert dust particles acting as effective ice nuclei at temperatures warmer than that required for homogeneous freezing was obtained from continuous flow diffusion chamber data . Different field and laboratory studies have shown that mineral dust aerosol particles act as effective ice nuclei in either deposition or condensation nucleation modes (Kumai 1961;Kumai and Francis 1962;DeMott et al 2003;Sassen et al 2003;Sassen 2005;Archuleta et al 2005;Diehl et al 2006;Field et al 2006;Kanji and Abbatt 2006;Knopf and Koop 2006;Möhler et al 2006;Salam et al 2006). Archuleta et al (2005) reported pure metal oxide and sulfuric-acid-coated metal oxide particles activated by heterogeneous ice nucleation at lower relative humidities than those required for homogeneously freezing of sulfuric acid solution particles with a continuous-flow ice thermal diffusion chamber.…”
Section: Introductionmentioning
confidence: 99%